An experience of the plasty of extremity bone defects in young children with tubostitis - Gritsay, Mykola; Vernigora, Ivan; Levitsky, Anatoly; Linenko, Oleksandr; Kisel, Nadejda; Tsokalo, Vasil (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article analyses immediate and remote results of treating young children, in whom tuberculous osteomyelitis of the extremity bones was diagnosed. The surgical treatment of 68 patients was provided by the authors themselves. Also, 10 children with orthopaedic complications resulting from tactical mistakes in the orthopaedic treatment at previous stages were observed. Removal of a specific focus of osteomyelitis in a bone before the process progressed into the phase of arthritis and the absence of any further orthopaedic complications (deformities and shortenings of extremity segments, stable contractures in the adjacent joints) were regarded as criteria of the positive result of the surgical treatment. The experience of the surgical treatment and the analysis of cases with the development of orthopaedic complications made it possible to draw conclusions, that positive functional results could be achieved only in case of the opportune surgical intervention, which consisted in the combination of the bone focus sanitation and plasty of the defect.